AI for arts - Hageback, Niklas; Hedblom, Daniel (AI for everything, 2022)
"What is artificial intelligence? What is art? How does AI influence art? AI for Arts is a book for anyone fascinated by the man-machine connect, an unstoppable evolution that is intertwining us with technology in an ever-greater degree, and where there is an increasing concern that it will be technology that comes out on top. Thus, presented here through perhaps its most esoteric form, namely art, this unfolding conundrum is brought to its apex, what is left of us humans if artificial intelligence surpasses us also when it comes to art? The articulation of an artificial intelligence art manifesto has been long overdue, so hopefully this book can fill a gap that will have repercussions not only for the aesthetic and philosophical considerations but possibly more so for the development of artificial intelligence"--